Military Reform and Militarism in Russia - Golts, Aleksandr; Kipp, Maia (Boulder : Lynne Rienner Publishers, 2018)
Aleksandr Golts traces the evolution of the Russian military, from the collapse of the Soviet Union to the incursions in eastern Ukraine in 2014-2017. Golts also sheds light on the reemergence of militarism in the Putin era, exploring its origins and making sense of the acceptance of the phenomenon by so much of Russian society.
Frontmatter -- Jamestown's Mission -- Table of Contents -- Acknowledgements -- Introduction: The Reform That Got Away From the Kremlin -- Chapter 1: A Vicious Circle -- Chapter 2: A Breakthrough and a Retreat -- Chapter 3: The Unfinished Reform -- Chapter 4: Military Reform in an Authoritarian State: The Prussian Case -- Chapter 5: The Country of Victorious Militarism -- Conclusion: Is Catastrophe Inevitable? -- Bibliography -- About the Author
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 01. Nov 2023).
eBooks on EBSCOhost
Keywords: Militarism -- Russia (Federation) -- History; Russia (Federation) -- Armed Forces -- Reorganization; POLITICAL SCIENCE / World / Russian & Former Soviet Union; Vladimir Putin, security